Long-term trends in the burden of colorectal cancer in Europe over three decades: a joinpoint regression and age-period-cohort analysis - Long, Dan; Mao, Chenhan; Zhang, Zhensheng; Liu, Yaxuan; Li, Jinru; Xu, Yin; Zhu, Ying (Frontiers in Oncology, 2023)
The burden of colorectal cancer (CRC) in Europe is at a high level, but the epidemiological features have not yet been systematically studied. This study aimed to provide a timely and reliable assessment of the burden and trends of CRC in Europe to provide a scientific basis for its prevention and treatment.We analyzed data on CRC in 44 European countries between 1990 and 2019 from the Global Burden of Disease study (GBD) 2019. In addition, the joinpoint regression model was applied to reflect temporal trends. The age-period-cohort model was constructed to explore age, period, and birth cohort effects that influence the risk of morbidity and mortality.In Europe, new cases, disability-adjusted life years (DALYs) and deaths of CRC rose by 70.01%, 22.88% and 38.04% from 1990 to 2019, respectively. The age-standardized incidence rate (ASIR) has increased, while age-standardized DALY rate and age-standardized mortality rate (ASMR) have declined. We found that men experienced a significantly higher CRC burden than women. Age-period-cohort analysis showed that the risk of incidence and mortality increased with age and time;and it was lower in the later-born cohort than the earlier-born cohort.ASIR for CRC in Europe generally trended upwards from 1990 to 2019, stabilizing in recent years but still at a high level. CRC burden varied considerably in different countries. There was a pronounced gender difference in CRC burden, and middle-aged and older men should be a priority population for CRC prevention and treatment.